APPROACHES TO THE UNDERSTANDING OF CIVIL SOCIETY IN THE WORLD OF THEORETICAL AND LEGAL THOUGHT - Філик, Н. В. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2007)
In this article the author investigates genesis of formation of the concept of civil society on the example of the analysis of theoretical developments of separate thinkers of the past and the present. Based on the analysis, the author identifies five main stages characterizing the development of the idea of civil society and the main moments of its formation in the practice of the state.